Climatic Variations Influenced Distribution and Productivity of Different Agroforestry Systems in Rajasthan, India - Singh, Bilas; Mahipal Bisnoi; Chouhan, Anil Singh; Kusum Lata Parihar; G Singh (Annals of Arid Zone, 2024)
Farmers of Rajasthan conserve and promote scattered trees and shrubs growing on farmlands to deal with climatic adversities. These woody perennials sustain livelihoods by providing economic, social, and environmental benefits. Tree-based farming systems were surveyed in all 10 agroclimatic zones (ACZs) of Rajasthan for screening best models and suggests for further improvement. Trees were assessed for density, and growth parameters in 0.5 ha plots, whereas agricultural crops yields were estimated in 1 m2 plots laid at 1 m from tree trunk, canopy edge and 5 m away from trees canopy (control). There were 107 tree-crop combinations involving 14 trees and 21 crop species. P. cineraria-based systems were dominant in the arid western, whereas A. nilotica dominated in semi-arid to dry sub-humid regions. Average tree density was 11.7 trees ha-1 ranging from 3.3 tree ha-1 in ACZ-IIIb to 23.6 tree ha-1 in ACZ-IIa. Senegalia senegal showed highest (27.6 tree ha−1) density. Height and canopy diameter were 11.73 m and 10.35 m respectively, in irrigated ACZ- IIIb and decreased to 6.53 m and 5.02 m in ACZ-IIb, respectively. Both height and density decreased with the decrease in rainfall from south-east to north-west. D. sissoo and T. grandis were taller, S. oleoides was thicker and Z. mauritiana was shorter and thinner than other species. Grain yields varied from 0.66 in ACZ-Ia to 1.85 Mg ha-1 in ACZ-IIIa, but exhibited low yield as compared to control. Crop yield reduced by 22.9-47.3% between ACZs, 20.3-56.5% between agroforestry systems, and 15.9-79.8% between intercrops highlighting the interactive effects of these components. S. senegal, T. undulata, P. cineraria, Z. mauritiana, S. oleoides, V. tortilis and P. juliflora based systems showed 29.1-54.9% low, whereas V. nilotica, D. sissoo, A. indica, T. grandis and V. leucophloea based systems showed 4.5-51.7% high yield over the state average. The yield of groundnut (IIIa), cotton (IVa), barley (IIIa), jowar (IVa), maize (IVa), paddy (V), pearl millet (IIIa) and wheat (V) with A. nilotica was above state average